RF wave coupling, plasma heating and characterization of induced plasma-material interactions in WEST L-mode discharges. (16th July 2021) - Urbanczyk, G.; Colas, L.; Hillairet, J.; Lerche, E.; Fedorczak, N.; Morales, J.; Gunn, J.; Ostuni, V.; Heuraux, S.; Vezinet, D.; Bobkov, V.; Desgranges, C.; et al.
Abstract: Plasma heating in the full tungsten (W) environment in a steady-state tokamak (WEST) relies on electromagnetic waves in both the lower hybrid (LH) and ion cyclotron range of frequencies (ICRF). The present study focuses mostly on the optimization of discharges heated with ICRF, by reporting different methods to first optimize wave coupling, optimize their absorption and reduce the impurity production. It is shown that ICRF coupling can be optimized by moving the plasma closer to antennas, increasing the plasma density, wave frequency and LH power. We show that the absorption efficiency correlates with the hydrogen concentration with the existence of an optimum between 7% and 10% as expected for a minority heating scenario. Absolutely calibrated visible spectroscopy sightlines were used to monitor ion fluxes in different locations as part of an effort to quantitatively estimate the contribution of different impurity sources to the core contamination by tungsten. It is typically found that in discharges with high total RF-power (above 5 MW of LH and 3 MW of ICRF), divertor and antenna limiter sources can reach a similar order of magnitude during the ICRF phase.